Comparative Efficacy of Oral Chinese Patent Medicine for Chronic Prostatitis/Chronic Pelvic Pain Syndrome With Sexual Dysfunction: A Bayesian Network Meta-Analysis of Randomized Controlled Trials - Zhang, Yang; Ma, Hongzhao; Nan, Tao; Li, Yongqiang; Zheng, Wei; Zhou, Zhihui; Gong, Xiaoyong (Frontiers in Pharmacology, 2021)
Background: Oral Chinese patent medicine (OCPM) combined with western medicine (WM) are believed to be effective for the therapy of chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) with sexual dysfunction (SD). These western medicines mainly involve antibiotics, phosphodiesterase type-5 inhibitor (PDE-5i), α-blockers. But there is no randomized controlled trial (RCT) that directly compares the efficacy of different OCPM. Hence, we operated a network meta-analysis (NMA) to contrast the efficacy of different OCPM for CP/CPPS with SD. Methods: Relevant studies were searched in PubMed, Cochrane Library, Web of Science, Embase, China National Knowledge Infrastructure (CNKI), Chinese Scientific Journal Database (VIP), and Wanfang database. All of the RCTs concentrated on the use of OCPM to cure CP/CPPS with SD from the inception of the databases to November 2020. We appraised the risk of bias under the Cochrane Handbook and CONSORT statement. The data were statistically analyzed via STATA 13.0 and WinBUGS 1.4.3 instrument. Results: Altogether, 30 pieces of literature with 2,996 participants containing 11 oral Chinese patent medicine and 11 interventions were included in the NMA. In terms of The National Institutes of Health chronic prostatitis symptom index (NIH-CPSI), Qianlie Shutong Capsules (QLSTC) + WM had the most possible of being the optimal treatment. In the light of the International Index of Erectile Function (IIEF-5), Congrong Yishen Granules (CRYSG) + WM had the most possible of being the optimal treatment. Shugan Yiyang Capsules (SGYYC) + WM performed the highest likelihood efficacy under cluster rank graph combined NIH-CPSI and IIEF-5. Liuwei Dihuang Pills/Yougui capsules (LWDHP/YGC) + WM had highly possible to be the optimal treatment not only for the clinical effective rate of CP/CPPS but also for the clinical effective rate of SD. Considering four outcomes, QLSTC, CRYSG, SGYYC, LWDHP/YGC, Qianlie Beixi Capsules (QLBXC) plus WM were the best therapy approach for CP/CPPS with SD, especially LWDHP/YGC + WM and QLBXC + WM. Conclusion: Based on the NMA, QLSTC, CRYSG, SGYYC, LWDHP/YGC, QLBXC plus WM demonstrated the maximum probability of being the optimal therapies. Owing to the limitations of this research, these results should be confirmed by elaborate RCTs. Systematic Review Registration: [https://www.crd.york.ac.uk/prospero/], identifier [CRD42021224060].